2015
DOI: 10.4103/0971-5851.151777
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco-related knowledge, attitudes, and practices among urban low socioeconomic women in Mumbai, India

Abstract: Context:Tobacco use is an important health issue globally. It is responsible for a large number of diseases and deaths in India. Female tobacco users have additional health risks.Aims:The aim was to assess changes in pre and post-intervention tobacco-related knowledge, attitudes, and practices among women from urban low socioeconomic strata, after three rounds of interventions.Subjects and Methods:A structured questionnaire was used to interview women living in low socioeconomic housing clusters in Mumbai, reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The results from this study confirm those of other studies in India in which HWLs have low levels of noticing and effectiveness [14, 30, 31, 34]. There are a number of possible reasons for this low level of effectiveness.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results from this study confirm those of other studies in India in which HWLs have low levels of noticing and effectiveness [14, 30, 31, 34]. There are a number of possible reasons for this low level of effectiveness.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the considerable evidence base linking SLT use with adverse health outcomes, knowledge of the health effects of SLT remains low [6, 13, 14]. Added to this, there are many misconceptions about SLT, including the belief among many that SLT can be used for health purposes, such as cleansing their teeth and to relieve stress and other health ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are also consistent with previous studies examining awareness of the harmful effects of tobacco use among tobacco users. Findings from both HICs and LMICs indicate that educational attainment and income are associated with knowledge of tobacco’s harmful effects [ 5 , 21 , 22 , 24 , 25 , 26 , 27 , 29 , 31 , 38 ]. This study extends those findings, noting a more general effect of lower health knowledge among vulnerable groups irrespective of tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it is not possible to assess whether improving the life circumstances of vulnerable groups will provide them with better skills to protect their health. However, a small intervention study of women living in one of Mumbai’s urban slums found that knowledge of the harms of tobacco increased following participation in the educational intervention [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date the enforcement of these policies has been weak to moderate [7] which is reflected in the increasing trend observed in our study especially among young adults. Increased awareness regarding tobacco use and oral cancer risk has been recently reported among urban slum women of Mumbai [35] , which could have an effect in future trends.…”
Section: Discussionmentioning
confidence: 99%